Crystal structures and temperature-dependent photoluminescence of lanthanide coordination frameworks of mixed-benzenedicarboxylates - Thammanoon Chuasaard (2020)
© 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group. A new series of non-porous, three-dimensional coordination frameworks, i.e. [LnIII(bdc)0.5(phth)(H2O)2], where LnIII = EuIII, TbIII, HoIII, ErIII and TmIII, phth2- = 1,2-benzenedicarboxylate, and bdc2- = 1,4-benzenedicarboxylate, were synthesized and characterized. The frameworks have two-dimensional sheets of which the stoichiometry is the same as the framework containing only phth2-. Architecture, topology and thermal stability of the frameworks were examined. Temperature-dependent photoluminescent properties of the EuIII and TbIII frameworks were studied and discussed with reference to those containing only phth2- and bdc2-. The mixed EuIII/TbIII frameworks were also prepared and their temperature-dependent photoluminescent properties were investigated, revealing energy transfer from TbIII to EuIII and its dependence on EuIII content.